Формування та використання інвестиційних портфелів підприємства - Саталкіна, Лілія Олександрівна (Національний університет "Львівська політехніка", 2016)
Дисертаційна робота присвячена вирішенню наукового завдання щодо розроблення теоретико-методологічних положень та практичних рекомендацій з забезпечення процесів формування та використання інвестиційних портфелів підприємств. Вперше розроблено метод використання інвестиційного портфеля підприємства на основі масштабно-якісної моделі та на засадах забезпечення розвитку підприємства. Сформовано визначення поняття «інвестиційний портфель підприємства», а також згруповано більш повну класифікацію інвестиційних портфелів підприємства, у якій передбачено їх принциповий поділ з точки зору виокремлення портфеля проектів та ресурсів. Удосконалено модель формування інвестиційного портфеля підприємства, а також типологію факторів формування та використання інвестиційного портфеля. Диссертационная работа посвящена решению научного задания по разработке теоретико-методологических основ и практических рекомендаций касательно формирования и использования инвестиционных портфелей предприятия. Впервые разработано метод использования инвестиционного портфеля предприятия на основе масштабно-качественной модели и базируясь на обеспечении развития предприятия. Сформировано определение понятия «инвестиционный портфель предприятия», а также сгруппирована более полная классификация инвестиционных портфелей предприятия, в которой предусмотрено их принципиальное разделение с точки зрения обособления портфеля проектов и ресурсов Усовершенствовано систему формирования инвестиционного портфеля предприятия, а также типологию факторов формирования и использования инвестиционных портфелей предприятия. Dissertation is devoted to the solution of scientific task that concerns the development of theoretically-methodological grounds and practical recommendations that relate to formation and utilization of enterprise investment portfolios. Scientific novelty of the obtained results consists in development of conceptual basis and practical recommendations of formation and utilization of enterprise investment portfolios. The object of the research refers to investment processes of machine-building enterprises. The subject of the research is theoretically-methodological and practical terms of machine-building enterprise investment portfolios formation and utilization. In the first chapter «Theoretically-methodological and conceptual terms of formation and utilization of enterprise investment portfolios» there is revealed the concept and significance of enterprise investment portfolio, there are formed the conceptual terms of enterprise investment portfolios formation and utilization, there are analyzed the processes of investment portfolios formation and utilization on machine-building enterprises. After careful studding of literary sources there was developed the concept of enterprise investment portfolio, which is proposed to be defined as a complex of investing resources at command of enterprise, which are used for the financing of enterprise productive and financial projects in such a way as to provide the development of enterprise in terms of investment activity. According to the proposed definition investment portfolio is characterized by the combination of such elements as: complex of investment resources, which are in command of enterprise (resource portfolio), and also the complex of projects of real and financial investment, that are financed by the noted resources with the aim to provide the development of enterprise (project portfolio). Also, concerning the peculiarities of the definition, there is represented the classification of enterprise investment portfolios with the following classification criterias: substantive component, the type of investments in the structure, the environment of investments orientation, the purposes of investment activity, the structure of investment resources, the influence of structure on stability, the ratio of revenues and expenses on formation. In the research there are developed the conceptual aspects of enterprise investment portfolio formation and utilization, which are reflected in the conceptual model. Conceptual model of enterprise portfolio formation and utilization is realized in such an order: determination of the complex aims of enterprise portfolio formation and utilization by responsible individuals; consistent implementation of formation and utilization processes in terms of the influence of factors, principles and with the aid of the basic tools. In the second chapter «Machine-building enterprise investment portfolios formation» there is developed the typology of factors that influence the process of enterprise investment portfolio formation, there are characterized the investment resources in portfolio structure, there is also developed the complex model of enterprise investment portfolio formation. One of the main aspects of scientific novelty of the dissertation refers to the determination of the main groups of factors that influence the process of investment portfolio formation. It is proposed to divide the groups of factors according to the level and the kind of their effect: factors of macro and micro level, factors of direct and indirect influence. We can point out such groups of factors of macro level of direct influence as: законодавчо-нормативні, економічні. Among the factors of macro level that effect indirectly we can find: political, international. The research contains the improved model of enterprise investment portfolio formation. The remarkable peculiarity of such a model is connected with isolation of two related processes: formation of resource portfolio and formation of project portfolio. Each of the two processes can be performed according to the aims, principles, factors of influence and with the aid of certain instruments. The result of the process of investment portfolio formation is connected with the development of the structure of investment resources that foresee the evaluation and analysis of their value, structure of the sources, and possible schemes of their combination considering their effect on the financial stability of enterprise. In the third chapter «Enterprise investment portfolio utilization» there are determined the main factors of enterprise investment portfolio utilization, there is proposed the system that will help to provide the development of enterprise in terms of investment portfolio utilization, there is developed the method of enterprise investment portfolio utilization that is based on scale-quality model. The enterprise investment portfolio utilization is connected with the process of choosing and financing of the complex of productive and financial projects, that correspond to the chosen directions of investment and provide the attainment of planned results as for the development of enterprise. Among the main factors that can determine the process of investment portfolio utilization it is possible to define two main groups: those, the influence of which concerns the organization of the enterprise investment portfolio utilization (informational, technical, professional, organizational) and also those that can characterize the main features of productive and financial projects and can effect the tactical aspects of enterprise investment portfolio utilization (special and economical). The nature of these factors is determined in dissertation. For the first time there is developed the method of enterprise investment portfolio utilization. The proposed method is based on a scale-quality model and are tended to provide the development of enterprise. Such a method is proposed to consider as the conclusive. Scale-quality model envisages the appreciation of the influence of certain projects on the level of enterprise development through the evaluation of certain indicators and refers to two stages: Stage 1 – financing of those projects that refer to the projects of internal investment, the aim of this stage is connected with the provision of the program of own enterprise development; Stage 2 – financing of the projects of external investment, the aim of this stage is connected with the obtaining of income, managerial benefits and others. The principal idea of such a model lies in the separation the two main motives of enterprise development: quantitative – an income, and qualitative – managerial benefits, quality of products, economy of resources.
Формирование и использование инвестиционных портфелей предприятий
Formation and utilisation of enterprise investment portfolio
Keywords: інвестиційний портфель; формування інвестиційного портфеля; використання інвестиційного портфеля; інвестиційний проект; проект внутрішнього інвестування; проект зовнішнього інвестування; инвестиционный портфель; формирования инвестиционного портфеля; использование инвестиционного портфеля; инвестиционный проект; проект внутреннего инвестирования; проект внешнего инвестирования; investment portfolio; investment portfolio formation; investment portfolio utilization; investment project; project of internal investing; project of external investing